Topological rigidity of quasitoric manifolds - Metaftsis, Vassilis; Prassidis, Stratos (MATHEMATICA SCANDINAVICA, 2018)
Quasitoric manifolds are manifolds that admit an action of the torus that is locally the same as the standard action of T^n on C^n. It is known that the quotients of such actions are nice manifolds with corners. We prove that a class of locally standard manifolds, that contains the quasitoric manifolds, is equivariantly rigid, i.e., that any manifold that is T^n-homotopy equivalent to a quasitoric manifold is T^n-homeomorphic to it.